(untitled) (Journal of Pathology of Nepal, 2017)
Background: Preeclampsia is associated with liver function abnormalities and renal function impairment. The objective of this study is to compare serum uric acid, glucose, calcium and magnesium in pre-eclampsia with normal pregnancy. Materials and Methods: Normal pregnant women and pre eclamptic women of age group 20-40 years were included. Serum magnesium, calcium, glucose, uric acid were analyzed. Results: Mean serum magnesium level in preeclampsia (1.83 ± 0.21mg/dl) was lesser in comparison to normal pregnant women (2.03 ± 0.16 mg/dl). Serum calcium level was lower (8.10 ±0.56mg/dl) than control (9.59 ±0.62 mg/dl) with p<0.001. Uric acid, glucose and lactate dehydrogenase in preeclamptic women was significantly higher than that in normal pregnant women (6.14 ± 0.85 vs.4.01 ± 0.62, p=<0.001), (94.17± 18.65 vs.86.34 ± 10.19, p=0.033) and ( 466.80 ± 97.29 vs. 194.22 ± 39.76, p=<0.001) respectively. Conclusion: There were significant changes in serum magnesium, uric acid, calcium, glucose, lactate dehydrogenase and total protein in pregnant women.